<span> x y
</span><span><span>−5</span><span>−9
</span></span><span><span>−4 -0</span></span><span>
</span><span><span>−3 3</span></span><span><span>
-2 0
-1-9</span></span>
Answer:
4(7+3)
Step-by-step explanation:
28 and 12 are both divisible by 4.
28 ÷ 4 = 7
12 ÷ 4 = 3
Answer:
4
Step-by-step explanation:
Brackets always mean "DO THIS FIRST!!!"
2+6 = 8
Then, do 3 x 8. That is 24.
24 divided by 4 is 6.
6 - 2 is 4!
Step-by-step explanation:
Derivation using Product rule : -
To find the derivative of f(x) = sin 2x by the product rule, we have to express sin 2x as the product of two functions. Using the double angle formula of sin, sin 2x = 2 sin x cos x. Let us assume that u = 2 sin x and v = cos x. Then u' = 2 cos x and v' = -sin x. By product rule,
f '(x) = uv' + vu'
= (2 sin x) (- sin x) + (cos x) (2 cos x)
= 2 (cos2x - sin2x)
= 2 cos 2x
This is because, by the double angle formula of cos, cos 2x = cos2x - sin2x.
Thus, derivation of sin 2x has been found by using the product rule.